Double Skin Façades and IoT: A Review of Their Role in Building Energy Conservation and Natural Ventilation - Khatri, Lachhman Das; Anakin , Chalin; Noah , Anderson; Prashansa, Sharma; Lamia Tasnim , Ankon (Urban Planning and Construction, 2024)
Double skin façades and the Internet of Things (IoT) are pivotal in enhancing a structure’s energy efficiency and natural ventilation. Their impact, however, varies based on design size and geographical location, prompting an exploration of the nuanced interplay between IoT technology and energy savings across diverse building types and climates. The paper emphasizes crucial considerations in assessing IoT’s impact on energy efficiency, such as building’s category and location, whether a towering skyscraper, a modest apartment complex in arid New Mexico, or a structure in frigid Alaska. Investigating whether one type outperforms others and discerning global prevalence becomes essential. The exploration delves into design challenges posed by different building categories, addressing questions about the nature of a particular type presenting intricate obstacles to efficient design and whether regulatory requirements limit creative possibilities. Additionally, it examines the adaptability of doubleskin façades concerning materials without compromising performance. Enhancing energy efficiency and indoor thermal comfort involves manipulating materials for façade skins, introducing characteristics like fabrics for outer skins to allow airflow, and mitigating heat radiation from inner skins made of concrete, glass, or metal. This time lag contributes significantly to maintaining ideal indoor thermal conditions. The integration of IoT technology is pivotal, generating real-time data and notifying users of temperature differentials. This data-driven approach ensures optimal façade operation compared to conventional methods. In conclusion, the paper underscores the critical relationship between IoT technology and energy conservation in diverse building categories and climates, shedding light on challenges and opportunities associated with energy efficiency design. It advocates for the intelligent use of materials and IoT technology to realize substantial energy savings and improved indoor comfort. Exploring design challenges and considerations provides valuable insights for practitioners in the field.